Accessibility and Use of Online Video Captions by Local Television News Websites. (December 2015) - Youngblood, Norman E.; Lysaght, Ryan
In July 2014, the Federal Communications Commission expanded broadcaster requirements for captioning online videos. The new guidelines, which go into effect in January 2016, require broadcasters to caption online clips from shows originally aired with captions. We conducted a content analysis and examined a stratified sample of one fifth of U.S. Designated Market Areas to see how prepared local TV news sites are for the rule changes and how accessible the sites are for users with disabilities. Barely 60% of sites captioned any of the sampled video clips and almost all sites had major accessibility issues.